Measurement of infiltration rates in urban sewer systems by use of oxygen isotopes - De Bénédittis, J (Water science and technology : a journal of the International Association on Water Pollution Research, 2005)
The paper presents the principle of a method to measure infiltration rates in sewer systems based on the use of oxygen isotopes and its application in Lyon (France). In the urban area of Lyon, significant differences in delta 18O that can reach 3 per thousand are observed between the oxygen isotopic compositions of groundwater originating from Rhone, Saone and from their associated alluvial aquifers. Drinking water supplying Lyon results mainly from pumping in the Rhone alluvial aquifer. Therefore, in some areas, the difference of isotopic composition between wastewater resulting from the consumption of drinking water and local groundwater can be used to measure infiltration in sewer systems. The application in the catchment of Ecully shows that the infiltration flow rate presents strong fluctuations at an hourly scale: it varies between 15 and 40 m3/h. This variability could be explained by non-constant discharges of pumping and by variations of the water level in the sewer